Awareness or Acquisition? Optimizing Genre-Based Writing Instruction for Post-Secondary L2 Writers - Anderson, Katherine (2017)
As English-medium universities grow increasingly multilingual, literacies support for domestic students and English language support for L2 writers become more and more enmeshed. Genre-based pedagogy is a common, and appropriate, approach to meeting these writers’ needs. However, little empirical research has been conducted on the effectiveness of genre-based writing instruction in post-secondary classrooms serving non-native English speakers. A survey of 20 studies on undergraduate and postgraduate L2 writers establishes that rhetorical awareness-raising, explicit instruction, and task play recurring and contested roles in determining learner outcomes. Although these topics align with key theoretical issues in second language acquisition, analysis suggests that developing expertise in understanding and handling genres may not happen in the same way as learning a language. Genrebased teaching methods may thus need to take additional care to make sure that the language learning needs of L2 writers are not overlooked. Three sets of learning materials demonstrate the author’s way of integrating these insights into traditional genre-based teaching approaches.